Strongyloidiasis stercoralis coinfection is associated with altered iron status biomarkers in tuberculous lymphadenitis - Kathamuthu, Gokul Raj; Rajamanickam, Anuradha; Sridhar, Rathinam; Baskaran, Dhanaraj; Babu, Subash (Frontiers in Immunology, 2022)
Soil-transmitted helminth [mainly Strongyloidiasis stercoralis (Ss)] and tuberculous lymphadenitis (TBL) coinfection in humans is a significant public health problem. We have previously shown that TBL+Ss+ coinfection significantly alters diverse cytokine, matrix metalloproteinase, and tissue inhibitors of metalloproteinase profiles. However, no data is available to understand the influence of Ss coinfection in TBL disease with respect to the iron status biomarkers. Hence, we have studied the effect of Ss coinfection on the circulating levels of iron status (ferritin, transferrin [TF], apotransferrin [ApoT], hepcidin, hemopexin) biomarkers in TBL disease. Our results show that TBL+Ss+ and/or TBL+Ss- individuals are associated with significantly altered biochemical and hematological parameters (red blood cell (RBC) counts, hemoglobin (Hb), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) were increased, and platelets were decreased) parameters compared to TBL-Ss+ individuals. Our results also show that TBL+Ss+ coinfection is associated with diminished circulating levels of ferritin, ApoT, hepcidin, and hemopexin compared to TBL+Ss- individuals. TBL+Ss+ and TBL+Ss- groups are associated with altered iron status biomarkers (decreased ferritin [TBL+Ss+ alone] and increased TF, ApoT, hepcidin and hemopexin [TBL+Ss- alone]) compared to TBL-Ss+ group. The heat map expression profile and principal component analysis (PCA) analysis of iron status biomarkers were significantly altered in TBL+Ss+ compared to TBL+Ss- and/or TBL-Ss+ individuals. A significant correlation (positive/negative) was obtained among the biochemical and hematological parameters (white blood cells (WBC)/ferritin, TF, and hepcidin mean corpuscular hemoglobin concentration (MCHC)/ferritin) with iron status biomarkers. Finally, receiver operating characteristic (ROC) analysis revealed that hemopexin was significantly associated with greater specificity and sensitivity in discriminating TBL+Ss+ and TBL+Ss- coinfected individuals. Thus, our data conclude that Ss coinfection is associated with altered iron status biomarkers indicating that coinfection might alter the host-Mtb interface and could influence the disease pathogenesis.